Dual-omics analysis reveals B vitamin regulation and metabolism in Areca Catechu inflorescence - Wenxiu Jiang; Xiaoxia Liu; Weiying Li; Jing Yang; Panjing Li; Minggeng Xie; Guangzhen Zhou (BMC Genomics)
Abstract Areca catechu flowers are an important component of traditional Chinese medicine for the treatment of various diseases. Studies on its secondary metabolites have largely focused on pyridine alkaloids yet a high-resolution metabolic profile of another important nutrient and coenzyme, the B vitamins, remains lacking. Here, we analyzed the levels of eight B vitamins in the inflorescence of A. catechu by targeted metabolomics. Our results showed that pantothenic acid and riboflavin were the predominant B vitamins, and that different B vitamins exhibited tissue-specific expression patterns within the various parts of the inflorescence. Furthermore, panoramic expression profiles of genes related to B vitamin biosynthesis in the inflorescence were mapped. Notably, we characterized a key rate-limiting enzyme in the thiamine biosynthesis pathway, the thiazole synthase (AcTHI1), that plays a crucial role in regulating thiamine biosynthesis. Additionally, integrated transcriptomic and targeted metabolomic analyses revealed hub transcription factors, including AcNAC73, AcMYB61, and AcARF9, that are associated with the regulation of pantothenic acid and thiamine metabolism. Taken together, our results lay a foundation for understanding the regulation of B vitamin metabolism during the development of A. catechu inflorescence and provide a theoretical basis for the development of the medicinal and nutritional potential of the plant.